2005
DOI: 10.1024/0300-9831.75.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-atherogenic Activities of Olive Oil Phenolics

Abstract: The aim of the current study was to investigate the antioxidant and cellular activity of the olive oil phenolics oleuropein, tyrosol, hydroxytyrosol, and homovanillic alcohol (which is also a major metabolite of hydroxytyrosol). Well-characterized chemical and biochemical assays were used to assess the antioxidant potential of the compounds. Further experiments investigated their influence in cell culture on cytotoxic effects of hydrogen peroxide and oxidized low-density lipoprotein (LDL), nitric oxide product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 39 publications
2
42
1
2
Order By: Relevance
“…Both HOTYR and HVAlc expressed much stronger protective effects than Trolox against LDL oxidation by extending the lag time of dienes formation to almost twice the concentration of 1 M (Fig. 2A), which was in agreement with previously reported data (Turner et al, 2005;Rietjens et al, 2007). In contrast, TYR appeared to have very weak activity in this model even at the highest concentration (10 M) ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Both HOTYR and HVAlc expressed much stronger protective effects than Trolox against LDL oxidation by extending the lag time of dienes formation to almost twice the concentration of 1 M (Fig. 2A), which was in agreement with previously reported data (Turner et al, 2005;Rietjens et al, 2007). In contrast, TYR appeared to have very weak activity in this model even at the highest concentration (10 M) ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Oxidation of low-density lipoproteins (LDLs) is a lipid peroxidation chain reaction, which is initiated by free radicals. It has been shown that hydroxytyrosol can inhibit LDL oxidation efficiently due to its capacity to scavenge peroxyl radicals (Arouma et al, 1998;Turner et al, 2005). Hydroxytyrosol reduces oxidation of the low-density lipoproteins carrying cholesterol (LDL-C), which is a critical step in the development of atherosclerosis and other cardiovascular diseases (Gonzalez-Santiago et al, 2010;Vázquez-Velasco et al, 2011); hydroxytyrosol has also a potential protective effect against oxidative stress induced by tertbutyl hydroperoxide (Goya et al, 2007).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Furthermore, The extracts from Geranium sanguineum L and Acacia species plants were also rich with polyphenol compounds and were found to exhibit a strong antioxidant, anti-mutagenic and radical scavenging capacities [43][44][45]. The antioxidant activities for each the Moldavian balm (Dracocephalum moldavica L), olive oil and A. chamaepitys essential oil were found to be as result of its contents of flavonoids and can be used in medicine and pharmacology for treatment of several diseases [46][47][48].…”
Section: Phenolic Compoundsmentioning
confidence: 99%